Comedy Western: film aesthetics and dramaturgy of the genre - Kosachova, Olga (ХДАК, 2025)
The Western as a film genre emerged in the early XX century, becoming one of the most characteristic forms of American cinema. Over the decades, however, the genre underwent transformations, reflecting social change, evolving audience expectations, and the development of the cinematic language itself. One such transformation is the comedy Western — a genre hybrid that combines the traditional traits of the classical Western with the dramaturgy of comedy.
Комедійний вестерн: кіноестетика та драматургія жанру
Keywords: вестерн; кіножанри